High yield fermentation of haemophilus influenzae and protein p6 expression: an approach to the production of a purified vaccine. part i (1998)
The present article describes an efficient, simple and unexpensive method for the production of high cellular densities of Haemophilus influenzae for cellular and cell free vaccine production. We present here a liquid culture-based method that had not been successfully implemented in Colombia, so far having given low yields and high costs. The kinetics, costs and production of the most promisory antigen candidates for vaccine production were evaluated in liquid and solid reference media.